2020
DOI: 10.31117/neuroscirn.v3i3.50
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism of BDNF Val66Met (rs6265) and its association to neuropsychiatric disorders

Abstract: Brain-derived neurotrophic factor (BDNF) is the most abundant neurotrophin in the central nervous system and was shown to be involved in neuronal growth, differentiation and synaptic plasticity. A single nucleotide polymorphism at the pro-region of the BDNF gene (rs6265) has been reported to alter the amino acid from valine to methionine at codon 66 and was associated with neuropsychiatric disorders in several studies. To date, the results on the association of BDNF rs6265 to the aetiology of the neuropsychiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 132 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…We observed that BDNF Val66Met allele dosage effects were more prominent in the right hippocampus, which may be associated with the hemispheric functional asymmetry of the hippocampus. It has been shown in human studies and animal models ( Chen et al, 2006 , Faris et al, 2020 , Montag et al, 2010 ) that the BDNF Met allele exhibits increased anxiety-related behaviors under stress, which in turn may increase the risk of psychiatric mood disorders, suggestive of gene ( BDNF Val66Met polymorphism) - environment (stress) interactions. Negative stimuli with aversive emotions tend to engage the right hippocampus more (Holt et al, 2005) for emotional processing ( Ahern and Schwartz, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that BDNF Val66Met allele dosage effects were more prominent in the right hippocampus, which may be associated with the hemispheric functional asymmetry of the hippocampus. It has been shown in human studies and animal models ( Chen et al, 2006 , Faris et al, 2020 , Montag et al, 2010 ) that the BDNF Met allele exhibits increased anxiety-related behaviors under stress, which in turn may increase the risk of psychiatric mood disorders, suggestive of gene ( BDNF Val66Met polymorphism) - environment (stress) interactions. Negative stimuli with aversive emotions tend to engage the right hippocampus more (Holt et al, 2005) for emotional processing ( Ahern and Schwartz, 1985 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) is the most abundant neurotrophin expressed in the central nervous system and was reported to be involved in neuronal growth and differentiation and synaptic plasticity, especially in the frontostriatal-cerebellar circuits and ventral striatal-limbic circuits (Faris et al 2020). These circuits are critical for the development of memory and visual motor integration abilities.…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism leads to deficient translocation and activity-dependent secretion of mature BDNF (Tsai 2018). It has been linked to impaired cognitive functioning in healthy adults and to several clinical features of many neuropsychiatric disorders such as major depressive disorder, Parkinson's disease, and Alzheimer's disease, in addition to diabetic patients (Bakusic et al 2021;Cagni et al 2017;Faris et al 2020;Miranda et al 2019). Performance of memory was one of the first cognitive domains to be extensively investigated for the influence of Val66Met polymorphism.…”
Section: Introductionmentioning
confidence: 99%